Thermo‐responsive block copolymer micelle‐supported (S)‐α, α‐diphenylprolinol trimethylsilyl ether for asymmetric Michael addition of nitroalkenes and aldehydes in water. Issue 7 (30th August 2020) - Li, Tao; Wang, Weilin; Wang, Songmeng; Liu, Lingyan; Chang, Weixing; Li, Jing
Abstract: An amphiphilic block copolymer PNIPAM53 ‐ b ‐(PS30 ‐ co ‐P4AMS10 ) was facilely prepared by reversible addition‐fragmentation chain transfer (RAFT) polymerization. The immobilization of ( S )‐α, α‐diphenylprolinol trimethylsilyl ether onto the block copolymers was then performed through using copper‐catalyzed alkyne‐azide cycloaddition (CuAAC), and the generating amphiphilic diblock copolymer supported chiral catalyst PNIPAM53 ‐ b ‐(PS30 ‐ co ‐P4AMS10 )/proTMS was self‐assembled into micelles with regular diameters about 50 nm in aqueous solution. The micellar catalyst was further used for the asymmetric Michael reaction between propanal and trans ‐β‐nitrostyrene in water. Using only 1 mol% micellar catalyst, the corresponding Michael addition products could be obtained in good yields and high enantioselectivities as well as good diastereoselectivities. In addition, this micellar catalyst could be reused at least for four times. Moreover, the micellar catalyst could be applied for the asymmetric addition reaction of 4‐chlorocinnamyl aldehyde and nitromethane, and thus constructing the baclofen pharmaceutical intermediate. Abstract :